The experience of using ataluren in Duchenne muscular dystrophy in Moscow: first results - T. N. Kekeeva; N. L. Pechatnikova; I. P. Vitkovskaya; V. S. Kakaulina; N. A. Krasnoschekova; Yu. E. Martynenko (Нервно-мышечные болезни, 2024)
Duchenne muscular dystrophy (DMD) is an X-linked inherited neuromuscular disorder typically manifesting in boys aged 2–5 years, characterized by a progressive course. According to natural disease progression data, individuals with DMD typically lose the ability to walk independently by the age of 13. In most cases, the disease leads to cardiorespiratory complications, resulting in a lethal outcome between the ages of 20–30.In recent years, there have been therapeutic agents developed for the pathogenic treatment of this condition. One such medication is ataluren (Translarna®), used in patients with DMD caused by the formation of a “stop codon” (nonsense mutation) in the DMD gene, responsible for the development of the disease.This article presents the experience of applying ataluren (Translarna®) in boys residing in Moscow who suffer from Duchenne muscular dystrophy.